THE MODEL DESIGN MODIFICATION OF SUNLIGHT DETECTION SYSTEM ON SOLAR CELL - Sutrisno Sutrisno; As'ad Aris Mustofa; Wawan Kusdiana; Okol Sri Suharyo (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
Indonesia is a country traversed by the equator therefore get a high intensity of sunlight from morning to afternoon, it can be utilized by utilizing solar power to be converted into electrical energy, that is using solar panels. The performance of solar panels is strongly influenced by the intensity of sunlight. Therefore it is Necessary to design a tool in the form of solar tracker that can move the solar panels to the position of the solar panels can always follow the direction of the coming sun. Currently there is already doing research with solar tracker but limited to move only east and west course, this will be more optimal if solar tracker can follow sunshine from all direction. In this research we managed to modify the models of a solar tracker that can move in direction east, west, north and south following the sun.The conclusion of this research is Obtained with the use of solar tracking system 2 degrees of freedom can reach a power increase of 11% Compared to the solar tracking system 1 degree of freedom. Keywords: Solar tracker 2 degrees of freedom, Solar cell.